Sustaining communication in collaborative learning environment - Abd Rahim, Normaliza; Jusoff, Kamaruzaman; Roslan, Siti Nur Aliaa (2011)
One of the ways for students in sustaining their communication in a collaborative learning environment is through hands-on activity. Therefore, the objectives of the study were to analyse the content of the communication among students involved and how they sustain their communication in the collaborative learning task given. Students were divided in pairs and they were tasked to design an animation made of clay with sound effects and script. The pair’s collaboration was taped and videoed in four weeks for the purpose of the study. Selected extracts of the communication during the task were discussed and analyzed in four stages; design the storyboard, making the figurines for animation, photography and video animation. The findings of the study revealed that students sustained their communication actively via continuous discussion in order to complete the given task. Collaborative learning was able to boost up students’ learning the media creative subject as well as allowing them to have high confidence in the task given. This study resulted in a positive impact towards sustaining students’ communication and to include collaborative learning as an activity for students to sustain their learning environment.